Effect of mitochondrial calcium uniporter blocking on human spermatozoa. (25th July 2014) - Bravo, A.; Treulen, F.; Uribe, P.; Boguen, R.; Felmer, R.; Villegas, J. V.
Summary Calcium (Ca2+) regulates a number of essential processes in spermatozoa. Ca2+ is taken up by mitochondria via the mitochondrial calcium uniporter (mCU). Oxygen‐bridged dinuclear ruthenium amine complex (Ru360) has been used to study mCU because it is a potent and specific inhibitor of this channel. In bovine spermatozoa, it has been demonstrated that mitochondrial calcium uptake inhibition adversely affects the capacitation process. It has been demonstrated in human spermatozoa that mCU blocking, through Ru360, prevents apoptosis; however, the contribution of the mCU to normal human sperm function has not been studied. Therefore, the aim of this study was to evaluate the effect of mCU blocking on human sperm function. Spermatozoa obtained from apparently healthy donors were incubated with 5 and 10 μm Ru360 for 4 h at 37 °C. Viability was assessed using propidium iodide staining; motility was determined by computer‐aided sperm analysis, adenosine triphosphate (ATP) levels using a luminescence‐based method, mitochondrial membrane potential (ΔΨm) using JC‐1 staining and reactive oxygen species (ROS) production using dihydroethidium dye. Our results show that mCU blocking significantly reduced total sperm motility and ATP levels without affecting sperm viability, ΔΨm and ROS production. In conclusion, mCU contributes to the maintenance of sperm motility and ATP levels in human spermatozoa.